Rare case of rectovaginal fistula in adults - Roy, Indrani; Shekar, Nithya; Pujari, Pran Singh (International Surgery Journal, 2021)
Rectovaginal fistula is an abnormal epithelial lined connection between the rectum and the vagina. The term anovaginal fistula may also be used when the internal fistula opening is found below the anorectal angle. Bowel contents leak through the fistula, allowing gas or stool to pass through the vagina. It may be congenital or acquired. Congenitally these are the anorectal malformations which affect the females when present since birth. Here, we have discussed the cases of adult rectovaginal fistula which the women had developed after vaginal delivery, the obstetric fistula. Patient presented with passage of stool from the vagina after the delivery. They were examined, assessed was successfully treated in our institution. Depending on the site of fistula formation, decision is taken for surgical approach and various techniques. Here the well-known Martius flap, which is based on bulbocavernosa muscle and pudendal artery has been used in both the cases. This flap is best used to repair fistula in the perineal region when there is no underlying sphincter defect.